Maghrib Learning Implementation at the Thousand One Cita Foundation - Latifah Zulaika; Muhammad Jais; Dafetta Fitrilinda; Daeng Ayub; Siti Ativai Putridian (Universitas Negeri Padang, 2026)
In order to achieve the national education goals, non-formal education initiatives are essential, especially when it comes to encouraging a love of learning outside of the classroom. The Seribu Satu Cita Foundation's Maghrib Belajar Program is one kind of real. This program aims to teach kids how to make the most of their after-school hours by studying, participating in educational events, and helping with homework in order to enhance their academic achievement, self-discipline, and religious character. Observation, documentation, and interviews are some of the data gathering methods used in this descriptive qualitative study. Problem identification, data collecting and analysis, and analysis of the study's results are the phases of the research process. The results of the study show that the Maghrib Belajar program is successfully implemented through non-disruptive planning, organizing, implementing, and monitoring procedures. In addition to improving children's learning and comprehension, this program cultivates self-discipline, a strong work ethic, and a drive to learn on their own. Lack of parental participation and inadequate infrastructure are two traits that should be mentioned, nevertheless. As a result, the Seribu Satu Cita Foundation's Maghrib Belajar Program may be among the best methods for encouraging kids' learning in a public setting.